Pelaksanaan Pembelajaran Seni Budaya (Tari Saman) di Kelas IX 6 SMP Negeri 34 Pekanbaru TA 2024/2025 - Mei Tasya Dwi Amanda; Laila Fitriah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This research aims to describe the implementation of cultural arts learning (saman dance) in class IX 6 of SMP Negeri 34 Pekanbaru. In this study, researchers used E. Mulyasa's (2013) learning theory. This type of research is a descriptive qualitative method, namely observation, interviews and documentation. The author made observations and then interviewed several sources. The author examines the documentation regarding the information data that the author has obtained. The research was conducted at SMP Negeri 34 Pekanbaru. The results of this research indicate that the implementation of cultural arts learning (saman dance) in class IX 6 of SMP Negeri 34 Pekanbaru is guided by the curriculum, syllabus and lesson plans. The curriculum used by SMP Negeri 34 Pekanbaru in class IX 6 is the 2013 curriculum which is implemented face to face. In preparing learning plans, arts and culture teachers are also guided by the 2013 curriculum which has been determined by the school and the syllabus is determined by the government and then adjusted to school conditions. The learning methods used are lecture, question and answer, discussion and practice methods. The media used when learning Cultural Arts (Saman Dance) are worksheets (students), printed books, and the internet. The tools used by teachers in teaching and learning activities are whiteboards, markers, assessment sheets, in focus, and speakers. The evaluations assessed by arts and culture teachers are the completeness of assignments, knowledge and skills.